Future Scenarios of Nursing Education in Iran - Alireza Nikbakht Nasrabadi; Abbas Ebadi; Masoud Fallahi-Khoshknab; Soheil Najafi-Mehri; Farideh Yaghmayi; Fatemeh Alhani; Atefe Vaezi; Mansoureh Sepehrinia; Mahboubeh Shali (Iran University of Medical Sciences, 2023)
Background & Aims One of the challenges in accurate and macro planning for the future is the uncertainty involved in estimating the future and rapid changes in various health-related fields. A powerful tool that can predict future competitive environments is the scenario planning tool. The current research aims to provide scenarios for the future of nursing education in Iran. Materials & Methods This exploratory research was conducted in 2022. In the first stage, the drivers and trends of nursing education were identified using meta-synthesis, interviews, and the Delphi method. Then, the influence and uncertainty of the identified trends were rated using the opinions of a panel of experts. In the next step, using influence/uncertainty diagrams, the key factors for writing the scenario were identified. Scenarios were then designed by Scenario Wizard software, version 4.11, and strategies were presented. Results The experts agreed on 6 drivers and 31 trends. With five key uncertainties, the scenarios were designed with three optimistic, realistic, and pessimistic assumptions. According to the size of the matrix and its dimensions (15×15), four problem-oriented, ethics-oriented, maintaining the status quo, and limited educational system scenarios were designed. The validity of the scenarios was examined according to feasibility, internal consistency, usefulness, and differentiability. Conclusion Each of the four designed scenarios has the potential to be realized, but their occurrence depends on the current plans. The use of future planning methods, such as the scenario planning tool, can be used as a warning system for awareness of opportunities and threats in Iran's health system before a crisis.